1998
DOI: 10.1093/hsw/23.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Access to Child Mental Health Services for Urban Children and Their Caregivers

Abstract: This article presents the results of a study that evaluated the effects of two engagement interventions on the initial attendance and ongoing retention in child mental health services of 109 primarily children of color and their families. Both the combined intervention (telephone and first interview) and the telephone-alone intervention were associated with significant increases in attendance at initial intake appointments over the usual intake procedure, but only the combined intervention was related to the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
128
4
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(140 citation statements)
references
References 35 publications
6
128
4
2
Order By: Relevance
“…Thus, developing effective and engaging interventions should be a high priority for those intervening with high-risk samples. To date, including this study, the extant literature does support the use of addressing pretreatment barriers to engagement as well as incorporating problem-solving treatment during BPT as methods to enhance engagement, and outcomes (Kazdin & Whitley, 2003;McKay, Stoewe, McCadam, & Gonzales, 1996;McKay et al, 1998;Pfiffner et al, 1990;Prinz & Miller, 1994). These components are relatively simple procedures and can be implemented as part of both group and individual BPT formats.…”
Section: Implications For Research Policy and Practicementioning
confidence: 84%
See 1 more Smart Citation
“…Thus, developing effective and engaging interventions should be a high priority for those intervening with high-risk samples. To date, including this study, the extant literature does support the use of addressing pretreatment barriers to engagement as well as incorporating problem-solving treatment during BPT as methods to enhance engagement, and outcomes (Kazdin & Whitley, 2003;McKay, Stoewe, McCadam, & Gonzales, 1996;McKay et al, 1998;Pfiffner et al, 1990;Prinz & Miller, 1994). These components are relatively simple procedures and can be implemented as part of both group and individual BPT formats.…”
Section: Implications For Research Policy and Practicementioning
confidence: 84%
“…First, the STEPP program incorporates an enhanced intake procedure that improves parents' motivation to engage in treatment, addressing possible practical barriers to treatment participation, and addressing maternal cognitions regarding expectations for treatment and attributions regarding their child's behavior (McKay, Stoewe, McCadam, & Gonzales, 1998;Morrissey-Kane & Prinz, 1999;Nock & Kazdin, 2005;Prinz & Miller, 1996). For instance, open-ended questions were asked of single mothers regarding their expectations about their as well as their child's involvement in treatment (e.g., What role do you think you will have in treatment?…”
Section: Methodsmentioning
confidence: 99%
“…), however, this has not typically been found in the adult treatment literature (Keijsers, Schaap, & Hoogduin, 2000). In addition, McKay, Stoewe, McCadam, and Gonzales (1998) found that therapist active engagement strategies with families, such as explaining the helping process, actively focusing conversation onto immediate and practical concerns, and directly addressing barriers to treatment, resulted in greater family retention into treatment. Coatsworth, Santisteban, McBride, and Szapocznik (2001) have also found evidence that directive Brief Strategic Family Therapy strategies, such as restructuring family interactions, assigning behavioral tasks, taking a leadership role in therapy, and providing a rationale for treatment, contribute to family members' engagement and retention in treatment.…”
Section: Therapist Direct Influence Skillsmentioning
confidence: 92%
“…Two studies on telephone-based interventions, one of fair-to-good quality and the other poor quality, both showed that TMH was successful, with follow-up study desirable. 25,26 A good-quality evaluation of cognitive-behavioural therapy for children with depression found that treatment was effective in both telemedicine and face-to-face groups, with a faster decline in the Children's Depression Inventory score for the telemedicine group. 27 A study comparing video conferencing, telephone, and face-to-face counselling for rural teenagers with epilepsy who had psychosocial difficulties did not find evidence that the mode of counselling influenced outcomes.…”
Section: General Psychiatric and Mental Health Servicesmentioning
confidence: 99%